Determinants of capital flight in Namibia - Tjaondjo, Cornelia Nangoi (Graduate School of Business (GSB), 2019)
The research investigated the determinants of capital flight and the behaviour of capital flight before and after the passage of Regulations 28 and 29 in Namibia. Using annual data form 1990 to 2016, the unit root and cointegration analyses were performed. The findings of the study indicate that foreign direct investment, current account deficit, change in foreign exchange reserves and external debt are important determinants of capital flight, whereas corruption and political uncertainty do not influence capital flight. The researcher therefore recommends that these factors should be taken into account when designing policies to prevent and reduce the outflows of capital from Namibia. Thus, the combination of good governance and fostering fiscal discipline and tax adjustments is also recommended.